The role of sodium – glucose cotransporter-2 inhibitors in the treatment of different phenotypes of chronic heart failure - M. Yu. Kolesnyk; Ya. Yu. Maistrovych (Сучасні медичні технології)
The number of patients with chronic heart failure syndrome is steadily increasing worldwide and Ukraine is not an exception. About 50 % of patients with heart failure have preserved ejection fraction of left ventricle. Recently, there has been significant progress in the diagnosis of this phenotype of heart failure, many diagnostic scales and practice-oriented algorithms have been developed, but the issue of treatment of chronic heart failure remains open.